ANALISIS HAMBATAN GURU DALAM MEMANFAATKAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) - Fadhila, Andi; Faisal, Muhammad; Syawaluddin, Ahmad (Universitas Negeri Makassar, 2025)
The type of research used is a case study, which is a research that is carried out intensively, in detail, and then in stages of an organization, institution or certain symptoms. This research aims to solve practical problems in daily life. This research was conducted at SDN 229 Pasaka, Sibulue District, Bone Regency. The focus of this research is the Analysis of Teachers' Obstacles in Utilizing Information and Communication Technology (ICT)-Based Learning Media related to teacher obstacles and their solutions. Data and data sources, namely primary data and secondary data obtained from informant or individual sources such as interview results and questionnaire results conducted by researchers. The analysis used is a qualitative analysis based on Data Collection, Data Display, Data Reduction, Conclusion: drawing/verifying or data summarization. There are several obstacles that occur by teachers when using media, namely, lack of teacher knowledge of technology, lack of teacher skills in managing time and making learning media, or teachers have more effective methods to be used in the teaching and learning process according to the material to be delivered. Efforts or efforts that can be made to overcome obstacles that occur to teachers when using media are the first to start from self-awareness to learn and gain insight into the latest technology, and teachers can take part in various trainings outside of school such as technical guidance or workshops on the use of learning media and technology.